Analisis Kepuasan Pengguna Aplikasi Peduli Lindungi Menggunakan Metode End User Computing Satisfaction - Hizryan Mohajerani; Beny Susanti (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2026)
The COVID-19 pandemic encouraged the Indonesian government to develop the PeduliLindungi application as a digital health service platform. This study aims to analyze user satisfaction with the PeduliLindungi application using the End User Computing Satisfaction (EUCS) method. The study employed a quantitative descriptive approach by distributing an online questionnaire to 400 PeduliLindungi users in the Jabodetabek area. The satisfaction dimensions analyzed include content, accuracy, format, ease of use, and timeliness.Data were analyzed using descriptive statistics and multiple linear regression. The results indicate that user satisfaction falls within the satisfied to very satisfied category, with the highest mean score on ease of use (4.415) and the lowest on content (4.197). Partially, accuracy, format, and ease of use have a significant effect on user satisfaction, while content and timeliness do not show a significant effect. Simultaneously, all EUCS dimensions have a significant effect on user satisfaction with the PeduliLindungi application.